Company Performance and Bond Rating: Evidence from Property, Real Estate dan Construction Companies in Indonesia - Kartadjumena, Eriana; Miftahuttaufiq, Grimal (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aimed to examine the effect of company performance proxied by ratios of liquidity, leverage, and asset growth on bond ratings of property, real estate, and construction companies listed in the Indonesia Stock Exchange during 2016-2019. The data were acquired from 40 financial reports of Ten Indonesian Companies in the property, real estate, and construction sectors and the bond rating issued by the Indonesian Securities Rating Agency, PT Pemeringkat Efek Indonesia (Pefindo).The data analysis technique was using the regression balanced panel data analysis. The results show that the company's liquidity had an insignificant negative effect on the bond rating; the company's leverage had an insignificant positive effect on the bond rating, while company growth had a significant negative effect on the bond rating.